Laccase activation in deep eutectic solvents - Toledo, Mariah L. (2020)
The research on alternative solvents and co-solvents is a relevant aspect when envisioning the improvement of biocatalytic reactions. Among these solvents and co-solvents, deep eutectic solvents (DES) may be considered as customizable new reaction media for biocatalysis. Accordingly, in this work, sixteen DES aqueous solutions, as well as of the individual DES components at the same conditions have been investigated in laccase-catalyzed reactions. Cholinium- and betaine-based DES formed with polyols at different molar ratio and concentrations were evaluated. The results reported show that in presence of most DES the laccase activity is preserved and, with a particular DES, enhanced up to 200%. Molecular docking studies demonstrated that while most DES components establish hydrogen-bonds with the enzyme amino acids, those that establish stronger interactions with the enzyme (expressed by absolute values of docking affinity energies) lead to an enhanced laccase activity. Finally, the laccase stability was evaluated in additional tests under extreme storage temperatures (60 ºC and -80 ºC). Although no significant protection to high temperatures was afforded by DES, an enhanced laccase activity when stored at low temperatures was found, at least up to 20 days. Combining experimental results and molecular docking this work shows that DES can be designed as co-solvents to improve biocatalytic reactions.